ALAT PENGUKURAN KELENGKUNGAN TULANG BELAKANG MANUSIA BERBASIS ARDUINO UNO. - Susanta, Muhamad Hilmansyah (LPPM Politeknik Pajajaran ICB Bandung, 2023)
Scoliosis is a spinal abnormality in the form of a lateral curvature which can be in the form of C or S. Scoliometer is a tool used in the examination of spinal abnormalities using the forward-bending method. Scoliosis can be detected in children at puberty (growth). Making tools in the title of this Final Project as a substitute for an electronic-based Scoliometer. This tool uses the MPU 6050 sensor as a Tilt sensor, Arduino Uno R3 Microcontrol as a data processor and the output of this tool in the form of an LCD screen as a sensor value and 3 LED lights (yellow, blue and red) as a result of inspection of tools in 3 categories, namely Normal, Intermediate and High Probability There is a difference in the slope between the tool and the tilt module (oblique object). Testing that is% error testing, at 10 at 1%, testing at 20 at 2%, testing at 30 at 3.3%, testing at 40 at 0.75%, testing at 50 at 1.2%, testing at 60 at 1.6% and testing at 70 is 1.1%.